2023
DOI: 10.1371/journal.pone.0281388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of footshock stress on social behavior and neuronal activation in the medial prefrontal cortex and amygdala of male and female mice

Abstract: Social behavior is complex and fundamental, and its deficits are common pathological features for several psychiatric disorders including anxiety, depression, and posttraumatic stress disorder. Acute stress may have a negative impact on social behavior, and these effects can vary based on sex. The aim of this study was to explore the effect of acute footshock stress, using analogous parameters to those commonly used in fear conditioning assays, on the sociability of male and female C57BL/6J mice in a standard … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Within the UN and SO control groups, we observed a higher degree of tail rattling responses to the SCS during extinction compared to the PA group, and tail rattling was more prominent during the tone period. Tail rattling has been observed in mice when determining hierarchical relationships (Haber and Simmel 1976, Terranova et al, 1998, Dorofeikova et al, 2023, anticipating fighting (Miczek et al, 2001), and encountering looming threat (Salay et al, 2018). Thus, tail rattling may be a behavior elicited in stressed mice that anticipate an uncertain threat.…”
Section: Discussionmentioning
confidence: 99%
“…Within the UN and SO control groups, we observed a higher degree of tail rattling responses to the SCS during extinction compared to the PA group, and tail rattling was more prominent during the tone period. Tail rattling has been observed in mice when determining hierarchical relationships (Haber and Simmel 1976, Terranova et al, 1998, Dorofeikova et al, 2023, anticipating fighting (Miczek et al, 2001), and encountering looming threat (Salay et al, 2018). Thus, tail rattling may be a behavior elicited in stressed mice that anticipate an uncertain threat.…”
Section: Discussionmentioning
confidence: 99%
“…However, rocking did not alleviate the decrease in mPFC neuronal activity but rather exacerbated it, suggesting that rocking may not produce anxiolytic effects by decreasing mPFC glutamatergic neuronal activity. However, it has also been reported that the administration of benzodiazepines to rats stimulated by plantar electroshock was able to reduce C-fos expression in the mPFC [37]. So further evidence is needed on what type of neurons these reduced activities are.…”
Section: Rocking Improves Hpa Axis Hyperresponsiveness In the Rat Acu...mentioning
confidence: 99%